Exploration of the Chetti culinary heritage and practices: the Peranakan Indian cuisine of Malaysia / Nurul Hanis Mohd Fikri - Mohd Fikri, Nurul Hanis (2022)
Chetti or Peranakan Indian cuisine is a hybrid of South Indian immigrants and Malay cuisines. The historical inter-cultural marriage between Indian traders and Malays, mainly local women during the 15th century and the Malacca Sultanate era has prompted the initial kickstart to the formation of the uniqueness of Chetti cuisine. This research focuses on identifying Chetti ethnic cuisine and to scrutinise the significance of its culinary heritage within the Chetti culture. The qualitative exploratory investigation was conducted mainly at the Chetti Village, Gajah Berang in Melaka through semi-structured interviews involving three different categories of Chetti informants: a sample of older Chettis, younger Chetti generations, and a mix of experts in Chetti culture from various backgrounds. A total of seven themes including three sub-themes were identified through thematic analysis. In essence, there are three major findings in this research. First, Chetti culinary heritage is an important cultural element of the various Chetti ceremonial events and festivals. Hence, it is an effective identity marker of the Chetti community. Second, the continuous social interaction with other ethnic groups particularly the Malays that went beyond the initial historical intercultural marriage has further infused the elements of Malay cuisine into the unique flavour and characteristics of the Chetti cuisine. Third, it was found that while the younger Chettis are proud and familiar with their ethnic cuisine, they are mostly unskilled in producing Chetti culinary heritage. The findings from this research will hopefully contribute to the scientific knowledge on minority ethnic cuisine particularly the Chetti cuisine as an important genetic code of Malaysian cuisine that mirrors the nation’s multicultural background. From a practical perspective, given the circumstances that Chetti cuisine is on the brink of extinction due to the dwindling of its population, it is crucial for the Chetti association and local government to continuously raise awareness about the hybrid cuisine. The findings indicate that cultural events involving exhibition of culinary heritage is effective in transmitting traditional food knowledge to the younger generation and subsequently assist in the preservation of traditional cuisines.